Women by Themselves collected by the Society of Women Writers - Lindsay, Hilarie (LiNQ (Literature in North Queensland), 2016)
Hilarie Lindsay reviews: Women by Themselves collected by the Society of Women Writers (Aust) Victorian Branch, Coles Publications pb, pp120, 9.95.